Contractors’ Attitude towards Enhancing Safety Performance: Case Study on Construction Firms in Penang - Md Ulang, N.; S., Ming Sing; Baharum, F.; Agus Salim, N.A. (EDP Sciences, 2014)
A qualitative study was conducted to investigate the contractors’ attitude towards enhancing the safety performance in construction site. Despite the fact that there are many safety initiatives established by the government, the rates of accidents are still in a critically high condition. Thus the purpose of this research is to study the contractors’ attitude towards enhancing the implementation of safety management system in construction site in order to increase the safety awareness of construction practitioners in construction site and improve the safety condition of construction sites. This study is conducted through oral interviews with the construction practitioners, and visual inspection of construction sites. The attitudes of contractors are evaluated from 3 aspects: Contractors’ efforts in implement and enforce the safety rules, Contractors efforts in overcoming the rate of accidents, and Reasons given by the contractors for not implement safety law.